SILENT MONSTER IN THE EAR: UNDERSTANDING THE LEVEL OF AWARENESS ABOUT CHOLESTEATOMA IN HOSPITAL VISITORS - Dr. Poornima S. Bhat; Dr. Nisha M.; Dr. Pravin Surendran; Dr. Santhanakrishnan Kaliavaradan; Dr. Shwetank Manjul; Dr. Rahul Panwar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Due to lack of severe symptoms and signs in initial stages and lack of awareness about the disease, there is a potential risk of uncomplicated cholesteatoma cases going unnoticed. This study aims to assess the level of knowledge about COM, especially cholesteatoma and related harmful practices among general population.Methods: All consenting adult hospital visitors, irrespective of their purpose of visit were invited to participate in this questionnaire based, cross sectional study at the preregistration point of the tertiary care teaching hospital. Data was collected and analyzed using appropriate methods. The questionnaire contained 7 categories of various questions related to ear infections, especially Cholesteatoma.Results: Among 350 respondents, majority exhibited poor level of knowledge about general perceptions about ear infections [295(84.3%)], perceptions about cholesteatoma [246(70.3%)]; awareness about intratemporal complications [244(69.7%)]; awareness about intracranial complications[247(70.6%)] and harmful practices in ear disease patients [279(79.7%)]. Multivariate analysis of socio-demographic and ear disease history related characteristics with overall ear disease related knowledge has shown that unskilled workers and unemployed respondents have poor knowledge levels compared to their counterparts, but at the same time the study has found that respondents with higher level of education also exhibited poor levels of knowledge in contrary to the existing evidence.Conclusion: This study highlights the lack of awareness about COM, especially cholesteatoma and its potential complications, harmful practices mainly in rural population, even in well educated groups, and the need for health education measures to create awareness among the general population regarding various areas of concern, to prevent a potential increase in the incidence of complications and deafness.